The 8-6-6 –Months Protocol: A Quick Method for Field Screening of Sugarcane to Smut - Marchelo-d’Raga, Philip W.; Bukhari, Khalid A. (University of Khartoum Journal of Agricultural Sciences, 2023)
This field study was conducted at the Sugarcane Research Centre at Guneid (latitude 150 N, longitude 330 E) for two consecutive seasons (2007/08 and 2008/09). The objective was to evaluate and validate the suitability of a new improved field evaluation method (IFEM) in comparison to the conventional field evaluation method (CFEM) which is widely used by pathologists worldwide in identifying resistant sugarcane genotypes to the smut disease. Nine sugarcane genotypes were tested, and sugarcane varieties CO 527, CO 997 and CO 6806 were used as checks. These experimental materials were inoculated artificially by two methods viz: i) Dip method (DM) and ii) Taiwanese pin-prick method (TPPM). Smut resistance evaluations by the new improved 8-6-6 field evaluation method, which took 20 months, identified 10 genotypes as highly resistant (HR) or resistant (R) using TPPM and 12 genotypes as HR or R using DM. The conventional 12-12-12 method (CFEM), which requires 36 months to complete, identified 9 genotypes as HR or R using TPPM and 10 genotypes as HR or R using DM. Differences between CFEM and IFEM were not significant in both DM and TPPM. Therefore, IFEM can be used confidently for routine evaluations of sugarcane germplasm as an alternative to CFEM, to efficiently save time and land.